1984
DOI: 10.1039/f19848002609
|View full text |Cite
|
Sign up to set email alerts
|

Surface area and the mechanism of hydroxylation of ionic oxide surfaces

Abstract: The nearly perfect {loo} surfaces of MgO smoke cubes formed in air do not show significant v(0H) absorption in infrared spectra from thin (10 mg cm-2), coherent films exposed to H 2 0 vapour for several hours. It is shown that perfect, five-fold-coordinated sites are not protonated and that the proportion of protonated, low-coordination (i.e. less than five-fold) sites is < 5%. These results are in accord with theoretical predictions for H, adsorption. In contrast, v(0H) [and v(CO,)] absorptions are observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
19
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…Previous ab initio calculations have shown that water molecules dissociate at surface defects, particularly steps and corners 12,14 , corroborating the observation that the reconstruction is more rapid if the surface is damaged 8 . The activation barrier for ion transport may be estimated given that the inverse reconstruction, the annealing of {100} facets on a (111) surface, is observed to occur at 1000K…”
Section: supporting
confidence: 55%
See 3 more Smart Citations
“…Previous ab initio calculations have shown that water molecules dissociate at surface defects, particularly steps and corners 12,14 , corroborating the observation that the reconstruction is more rapid if the surface is damaged 8 . The activation barrier for ion transport may be estimated given that the inverse reconstruction, the annealing of {100} facets on a (111) surface, is observed to occur at 1000K…”
Section: supporting
confidence: 55%
“…They showed that dissociative chemisorption is energetically unfavourable and that physisorption of intact water molecules is preferred. This was confirmed by a CarParrinello ab initio molecular-dynamics study 12 instead at low co-ordinated sites such as steps, corners and other defects 8,13 and dissociation was demonstrated computationally at steps and corners 12,14 . However one might expect this to simply saturate the defect sites.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…In each case, it was assumed that the density of reactive sites per unit area is constant and independent of the extent of dissolution or of pH. * This assumption is certainly not true of the initial stages of dissolution of MgO where the reactivity is govemed by the rapidly changing structure of the oxide surface [11,12,14]. A dramatic restructuring of the smooth, nearly perfect (100) MgO smoke faces occurs before any significant dissolution (i.e.…”
Section: O>(s) + H + (Aq) -+ Oh(s)mentioning
confidence: 99%